Public Health Detailing to Increase Routine HIV Screening in Baltimore, Maryland: Satisfaction, Feasibility, and Effectiveness. (November 2017) - Safi, Amelia Greiner; Perin, Jamie; Mantsios, Andrea; Schumacher, Christina; Chaulk, C. Patrick; Jennings, Jacky M.
The objective of this study was to evaluate the satisfaction with, and the feasibility and effectiveness of, a public health detailing project focused on increasing routine human immunodeficiency virus (HIV) screening of people aged 13-64 by primary care providers working in areas of Baltimore City, Maryland, with high rates of HIV transmission (defined as a mean geometric viral load of ≥1500 copies/mL per census tract). In public health detailing, trained public health professionals (ie, detailers) visit medical practice sites to meet with providers and site staff members, with the intention of influencing changes in clinical practice policy and/or behavior. During 2014, detailers made personal visits and gave HIV Testing Action Kits containing maps, educational and guideline documents, and resource lists to 166 providers and office managers at 85 primary care sites. At follow-up, 88 of 91 (96.7%) providers and 37 of 38 (97.4%) clinic managers were very satisfied or satisfied with the project. Of the 79 sites eligible at follow-up (ie, those that had not closed or merged with another practice), 76 (96.2%) had accepted at least 1 HIV Testing Action Kit, and 67 of 90 (74.4%) providers had increased their HIV screening. Public health detailing projects can be used to educate and support providers, establish relationships between providers and local health departments, and disseminate public health messages.